Lithuanian nurses’ organisation – challenges and opportunities experienced by nurses - Volodkaitė, Aušra (Slauga. Mokslas ir praktika, 2021)
The Lithuanian Organization of Nursing Specialists (hereinafter - LNO) was established on December 19, 1992 during the Congress held by nursing professionals. Currently LNO is the largest professional branch organization and trade union of nurses, which brings together nurses from health care institutions of Lithuania, represents nursing professionals in various institutions and defends their professional, labour, economic, social rights and interests. The mission of LNO is to bring together nursing professionals, to improve the social and work conditions of nurses and to strengthen solidarity. Key operational priorities of LNO: • Participation in national health policy • Representation of interests of nursing professionals at all levels • Initiation, implementation, development of social dialogue • Continuous education, consultations and delivery of information for nurses • Cooperation and collaboration with the social partners in order to influence: ▪ Legal regulation and self-regulation of nursing profession ▪ Development of nursing services and improvement of pricing system ▪ Development knowledge, skills, competencies and motivation of nurses ▪ Leadership development LNO as a social partner contributes to the development of social dialogue at all levels - in institutions, regions, and at the national level, working with social partners, employers’ organizations, official state institutions. The development of social dialogue and achieved agreements bring benefits for all members. Protection and representation of nurses are one of the major goals. LNO provides support and assistance for nurses during difficult periods: e.g. COVID-19 pandemics, times of crisis, reorganization of health system. Trade union monitors situation in healthcare institutions, provide consultations and information, negotiates with employers, discuss ways of solutions. LNO cooperates with representatives of universities, colleges, health care institutions, State institutions, other trade unions. LNO is a member of the largest international nursing organizations. International cooperation is very important. Nurses can share their experience with international colleagues during online meetings, seminars. Also leaders can talk about professional issues and ways to influence important changes in nursing profession.